PENGARUH CAPAIAN PEMBELAJARAN PRAKTIK KERJA INDUSTRI DAN PENGENALAN LAPANGAN PERSEKOLAHAN (PLP) TERHADAP EMPLOYABILITY SKILLS MAHASISWA PENDIDIKAN TEKNIK BANGUNAN SEBAGAI CALON GURU - Fadli Syarief Darmadi; Isnandar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the influence of Industrial Work Practice (IWP) and School Field Introduction Program (SFIP) learning outcomes on the employability skills of Building Engineering Education (BEE) students as prospective teachers. This study used a quantitative approach with an ex post facto design. The population consisted of BEE students from the 2022 cohort who had completed both IWP and SFIP, with 70 respondents determined through a census technique. Data were collected using a 1–5 Likert-scale questionnaire distributed online via Google Forms, then analyzed using multiple linear regression assisted by SPSS. The results show that IWP learning outcomes have a positive and significant effect on employability skills (B = 0.484; Sig. = 0.001), and SFIP learning outcomes also have a positive and significant effect (B = 0.491; Sig. = 0.002). Simultaneously, IWP and SFIP significantly affect employability skills (Sig. = 0.001), contributing 58.6% (R² = 0.586), while the remaining 41.4% is explained by other factors outside the study. These findings confirm that IWP equips students with technical readiness, discipline, and industrial professionalism, while SFIP strengthens pedagogical and social competencies as prospective teachers. Both programs complement each other in producing graduates who are ready to enter the workforce, either as educators or as professionals in the construction sector